Penyesuaian Sosial Pada Murid Eks-Lesbian dan Penanganannya (Studi Kasus di UPT SMPN 33 Makassar) - Rosdiana; Sahril Buchori; Aswar; Syahril (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to examine social adjustment in terms of the participation aspect related to involvement in social relationships, the contributing factors, the impacts, and the counseling process using the cognitive restructuring technique for a student with same-sex relationship experiences at SMPN 33 Makassar. This research employed a qualitative clinical case study approach. Data were collected through in-depth interviews, observation, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing, while trustworthiness was ensured through triangulation, peer review, and intersubjective validity. The findings revealed that the social adjustment of the participant, EIN, tended toward maladjustment, characterized by social withdrawal, limited social interaction, passive behavior, and difficulties in establishing friendships. These behaviors were associated with social rejection, social anxiety, negative labeling, and a lack of family support. The resulting impacts included psychological distress, decreased learning motivation, reduced self-confidence, and lower social participation at school. Counseling using the cognitive restructuring technique demonstrated positive changes in supporting the participant's social adjustment process within the school environment